Wear pattern of various router bit material in cutting rubberwood medium density fibreboard / Muhammad Kamal Ariffin Badrun - Badrun, Muhammad Kamal Ariffin (1999)
In order to study the wear pattern of various router bit material in cutting Rubberwood Medium Density Fibreboard (MDF), two kinds of router bit material (High Speed Steel and Tungsten Carbide Tipped) were employed in cutting Rubberwood MDF. The TCT showed the longest working life (twice the cutting distance compared to the HSS), while the HSS retained its usefulness for only a short distance of cutting. In the testing, using the Tungsten tipped and the Steel tipped, it was also confirmed that the Steel tipped wore more than the Tungsten tipped. From the observation of the worn tips it was found that the most useful in cutting Rubberwood MDF is the TCT, although for the HSS is best suitable for cutting solid wood as for the finish surface is more smooth if the HSS is to be sharped by honing it. There are many constraining in this testing as the wear mechanism and the wearing processes of those router bit materials are discussed.